Recent converts aspiring for ordination: Canon 1042 - Woestman, William H. (CLSA advisory opinions, 2001-2005, 2001)
Several members of the RCIA program in our diocese have expressed serious interest in becoming permanent deacons and another wants to begin studies for the priesthood. Does the simple impediment found in canon 1042, 3° preclude their beginning immediately preparation for ordination since it will be at least three years before any of them finish the formation program for the permanent diaconate, and at least four years before the aspiring seminarian would be ordained to the priesthood?